Efektivitas Kepemimpinan Wanita Dalam Mengatasi Konflik Sosial (Studi Pada Kepemimpinan Bupati Kabupaten Bima Dalam Satu Periode) - Mardiah Mardiah; Abdul Kharis; Lies Sholihah (JIAP (Jurnal Ilmu Administrasi Publik), 2018)
West Nusa Tenggara Province is an area headed by female leaders, namely Bima district known as the "Red Zone" of conflict prone areas. Indah Damayanti Putri or who is familiarly called Dae Dinda became the first woman in Bima who served Regent. Social conflicts that become a complicated problem in Kabupaten Bima is a challenge for a leader in finding a solution. The purpose of this research is to know the effectiveness of Bima regent leadership in handling social conflict. The method used in this research is qualitative method with descriptive approach. The results of this study indicate that the leadership of Bima district regency is considered very effective, it is measured from several indicators, namely the character / personality of leaders, leadership motivation and competence / ability in the lead. The success is evidenced by the decrease in the number of conflicts and the quality of the weakened conflict that is the conflict caused by teenagers fight is no longer a large conflict between groups such as conflict between villages.